2022
DOI: 10.3390/ph15091055
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Does Not Show Major Hidden Cardiotoxicity in Models of Ischemia/Reperfusion but Abolishes Ischemic Preconditioning-Induced Antiarrhythmic Effects in Rats In Vivo

Abstract: Clinical observations are highly inconsistent with the use of the antidiabetic rosiglitazone regarding its associated increased risk of myocardial infarction. This may be due to its hidden cardiotoxic properties that have only become evident during post-marketing studies. Therefore, we aimed to investigate the hidden cardiotoxicity of rosiglitazone in ischemia/reperfusion (I/R) injury models. Rats were treated orally with either 0.8 mg/kg/day rosiglitazone or vehicle for 28 days and subjected to I/R with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…To enable the identification of drugs that are possible candidates of drug repurposing for a novel indication in HF, we aimed to identify GPCRs that show significantly different expression in TAC vs. SHAM hearts, as GPCRs are the largest family of targets for already-approved drugs—agonists, antagonists or partial agonists—currently available on the market. Given the general need for increasing translational value and success of preclinical studies in the field of cardiology [ 29 , 30 , 31 , 32 , 33 ], we aimed to conduct a systematic screening of cardiac GPCRs with reduced risk of subjective bias. To this end, we first assessed the cardiac GPCR gene expression both by bulk RNA sequencing and ddPCR, and filtered only for those candidates that (i) were identified by both methods to be significantly differentially expressed in TAC vs. SHAM rat hearts, and (ii) show significant correlation in levels of gene expression measured by both methods.…”
Section: Discussionmentioning
confidence: 99%
“…To enable the identification of drugs that are possible candidates of drug repurposing for a novel indication in HF, we aimed to identify GPCRs that show significantly different expression in TAC vs. SHAM hearts, as GPCRs are the largest family of targets for already-approved drugs—agonists, antagonists or partial agonists—currently available on the market. Given the general need for increasing translational value and success of preclinical studies in the field of cardiology [ 29 , 30 , 31 , 32 , 33 ], we aimed to conduct a systematic screening of cardiac GPCRs with reduced risk of subjective bias. To this end, we first assessed the cardiac GPCR gene expression both by bulk RNA sequencing and ddPCR, and filtered only for those candidates that (i) were identified by both methods to be significantly differentially expressed in TAC vs. SHAM rat hearts, and (ii) show significant correlation in levels of gene expression measured by both methods.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our group has shown that using preclinical models of I/R injury could be suitable to detect hidden cardiotoxic effects of drugs. In a rat model of myocardial I/R injury, 28 days of rofecoxib pretreatment was found to increase the mortality and irreversible ventricular fibrillations during cardiac ischemia [ 3 ]; thus, it showed hidden cardiotoxic effects according to our definition, while we have found that the PPAR-γ agonist antidiabetic drug, rosiglitazone, does not show major hidden cardiotoxic effects, but it interferes with the antiarrhythmic effect of ischemic preconditioning [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…the ISs (as proportions of AARs in %) and AARs (as proportions of total left ventricular areas in %), was measured with computer planimetry by independent and blinded investigators using InfarctSize software (version 2.4b, Pharmahungary Group, Szeged, Hungary) in the Budapest and Szeged study centres, or SigmaScan Pro 5 (Systat software, San Jose, CA) in the Amsterdam study centre, as described in previous publications of the workgroups. [27][28][29][30][31][32][33][34][35]…”
Section: Is Measurementmentioning
confidence: 99%